On the collaborative design and simulation of space camera: stop structural/thermal/optical) analysis - Duan, Pengfei; Lei, Wenping (SPIE, 2017)
A number of disciplines (mechanics, structures, thermal, and optics) are needed to design and build Space Camera. Separate design models are normally constructed by each discipline CAD/CAE tools. Design and analysis is conducted largely in parallel subject to requirements that have been levied on each discipline, and technical interaction between the different disciplines is limited and infrequent. As a result a unified view of the Space Camera design across discipline boundaries is not directly possible in the approach above, and generating one would require a large manual, and error-prone process. A collaborative environment that is built on abstract model and performance template allows engineering data and CAD/CAE results to be shared across above discipline boundaries within a common interface, so that it can help to attain speedy multivariate design and directly evaluate optical performance under environment loadings. A small interdisciplinary engineering team from Beijing Institute of Space Mechanics and Electricity has recently conducted a Structural/Thermal/Optical (STOP) analysis of a space camera with this collaborative environment. STOP analysis evaluates the changes in image quality that arise from the structural deformations when the thermal environment of the camera changes throughout its orbit. STOP analyses were conducted for four different test conditions applied during final thermal vacuum (TVAC) testing of the payload on the ground. The STOP Simulation Process begins with importing an integrated CAD model of the camera geometry into the collaborative environment, within which 1. Independent thermal and structural meshes are generated. 2. The thermal mesh and relevant engineering data for material properties and thermal boundary conditions are then used to compute temperature distributions at nodal points in both the thermal and structures mesh through Thermal Desktop, a COTS thermal design and analysis code. 3. Thermally induced structural deformations of the camera are then evaluated in Nastran, an industry standard code for structural design and analysis. 4. Thermal and structural results are next imported into SigFit, another COTS tool that computes deformation and best fit rigid body displacements for the optical surfaces. 5. SigFit creates a modified optical prescription that is imported into CODE V for evaluation of optical performance impacts. The integrated STOP analysis was validated using TVAC test data. For the four different TVAC tests, the relative errors between simulation and test data of measuring points temperatures were almost around 5%, while in some test conditions, they were even much lower to 1%. As to image quality MTF, relative error between simulation and test was 8.3% in the worst condition, others were all below 5%. Through the validation, it has been approved that the collaborative design and simulation environment can achieved the integrated STOP analysis of Space Camera efficiently. And further, the collaborative environment allows an interdisciplinary analysis that formerly might take several months to perform to be completed in two or three weeks, which is very adaptive to scheme demonstration of projects in earlier stages.